Audiovisual prior entry. - Zampini, M; Shore, D; Spence, C (2005)
It is almost one hundred years since Titchener [E.B. Titchener, Lectures on the Elementary Psychology of Feeling and Attention, Macmillan, New York, 1908] published his influential claim that attending to a particular sensory modality (or location) can speed up the relative time of arrival of stimuli presented in that modality (or location). However, the evidence supporting the existence of prior entry is, to date, mixed. In the present study, we used an audiovisual simultaneity judgment task in an attempt to circumvent the potential methodological confounds inherent in previous research in this area. Participants made simultaneous versus successive judgment responses regarding pairs of auditory and visual stimuli at varying stimulus onset asynchronies (SOAs) using the method of constant stimuli. In different blocks of trials, the participants were instructed to attend either to the auditory or to the visual modality, or else to divide their attention equally between the two modalities. The probability of trials containing intramodal stimulus pairs (e.g., vision-vision or audition-audition) was increased in the focused attention blocks to encourage participants to follow the instructions. The perception of simultaneity was modulated by this attentional manipulation: Visual stimuli had to lead auditory stimuli by a significantly smaller interval for simultaneity to be perceived when attention was directed to vision than when it was directed to audition. These results provide the first unequivocal evidence for the existence of audiovisual prior entry.